Drogas de abuso em águas naturais e residuárias urbanas: ocorrência, determinação e aplicações forenses - Feitosa, Rafael Silva (2013)
Drugs of abuse are commonly used outside medical or legal settings where their production, marketing and consumption are subject to legal summons and/or intervention. Classified as emerging contaminants, these substances have been recently detected in samples of environmental concern, such as waters and wastewaters. This review presents the state-of-the-art on the methodological approaches used in sample preparation, the main techniques applied in analytical determination at trace levels, as well as the use of information related to the drug or its metabolite concentration in sewage samples to empirically estimate the consumption of drugs of abuse in a city or region.